MESIN BRIKET SAMPAH ORGANIK SEBAGAI ALTERNATIF SUMBER ENERGI BIOMASSA MENUJU LINGKUNGAN BERSIH: PEMBERDAYAAN MASYARAKAT - Kandou, S.B.T.; Hutapea, J.N.; Putra, I.G.N.A.A.M.; Gunawan, I.G.N.W.; Ndabung, A.F.; Komaladewi, A.A.I.A.S. (Buletin Udayana Mengabdi; Vol 20 No 4 (2021): Buletin Udayana Mengabdi, 2022)
Integrated Waste Processing Site (TPST) 3R Werdhi Guna, District of Klungkung has a large quantity of solid waste for about 1 ton per day, which the waste processing method is still depending on waste burning. This creates dangerous smoke that affects surrounding environment. Refers to that, this social empowerment is done to educate partners in order to utilize organic waste into briquettes as an energy source. This empowerment program will be carried out in six stages: occupational health & safety and waste sorting training, waste composting training, waste cropping training, briquette standardization, waste briquetting training, and training on the application of briquettes towards traditional stove. The pre-test and post-test are used as benchmarks for competency of waste processing theory, while practical competencies are proven through the production of organic waste briquettes produced by briquette machine. The results obtained were an increase in the test value of 70.5% and 150 kg of produced briquette with calorific value of 4054.86 cal/gr.